Analisis Pendekatan Kognitif Dalam Penanganan Kurangnya Motivasi Belajar Remaja - Pradiva, Diva; Karnianti, Asniar; Qudratullah, Qudratullah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Low learning motivation among adolescents has become a significant issue in modern education, particularly due to increasing digital distractions and cognitive changes during developmental stages. This study employs a qualitative method through library research to analyze how the cognitive approach explains the factors contributing to low learning motivation, including negative thinking patterns, low self-efficacy, and dysfunctional attributions. The findings indicate that maladaptive beliefs and a fixed mindset significantly reduce adolescents’ academic engagement, while cognitive interventions such as cognitive restructuring, self-efficacy enhancement, and metacognitive training effectively improve learning motivation. In addition to internal factors, excessive exposure to digital media also worsens self-regulation and attention. These results highlight that the cognitive approach is a relevant and effective strategy to enhance adolescents’ learning motivation by modifying their thought patterns and strengthening self-regulatory abilities